The Impact of Audiovisual-Assisted Project-Based Learning and Motivation on Drama Writing Skills in Vocational High School Students - Serly Fatiyas; Nurizzati Nurizzati (AL-ISHLAH: Jurnal Pendidikan, 2025)
This experimental study examines the effectiveness of Project-Based Learning (PBL) integrated with audiovisual media in enhancing students’ drama writing skills and learning motivation in a vocational high school setting. The research was conducted at SMK Negeri 7 Batam during the 2024/2025 academic year, involving Grade XI students selected through purposive sampling. A total of 83 students participated, with Class XITKL5 assigned as the experimental group receiving PBL instruction assisted by audiovisual resources, and Class XITKL3 as the control group receiving conventional, teacher-centered instruction. Employing a 2×2 factorial design, data were collected through a performance-based drama writing test and a validated motivation questionnaire. Statistical analyses, including t-tests and two-way ANOVA, were conducted using IBM SPSS Statistics 25 to assess the main and interaction effects. The results revealed that students in the experimental group significantly outperformed those in the control group in drama writing performance. Furthermore, a significant interaction effect was identified between instructional model and learning motivation, indicating that students with higher motivation benefited more from the PBL-audiovisual approach. However, even students with lower motivation showed improvement compared to their counterparts in the control group. These findings highlight the pedagogical value of integrating audiovisual media within a project-based framework to foster creativity, engagement, and skill development in writing. The study contributes to the implementation of Indonesia’s Merdeka Curriculum by offering an innovative, student-centered strategy suitable for vocational education contexts.